Efektivitas Kepemimpinan PJ Wali Nagari terhadap Pelaksanaan Fungsi Pembangunan di Nagari Kajai - Fero Andika; Wahib Assyahri; Diga Putri Oktaviane (Jurnal Administrasi Publik dan Pemerintahan, 2026)
This study aims to analyze the effectiveness of the leadership of Acting (PJ) Wali Nagari in the implementation of development functions in Nagari Kajai, Talamau District, West Pasaman Regency. From 2016 to 2025, the nagari experienced ten leadership turnovers without a definitive Wali Nagari, resulting in discontinuity of development programs, low community participation, and weak leadership legitimacy. This study employed a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and documentation involving seven groups of informants. Data analysis was conducted using Duncan’s organizational effectiveness theory (as elaborated by Steers, 1985), which includes goal achievement, integration, and adaptation dimensions, supported by situational leadership theory by Hersey and Blanchard (1982). The results indicate that the leadership effectiveness of the Acting Wali Nagari is moderately effective but uneven. Physical development programs showed an increasing trend from 68% to 87%, while community empowerment programs declined from 52% to 38%. In addition, the phenomenon of “participation fatigue” resulted in low community attendance in Musrenbang (33.75%) and limited idea generation (19.4%). From a situational leadership perspective, Telling and Selling styles were effective in physical development programs; however, the Delegating style was applied prematurely in empowerment programs. This study recommends improving the selection mechanism of Acting leaders, strengthening orientation programs, and accelerating the election of a definitive Wali Nagari